Noise Figure Modeling Subject to Frequency and Temperature for AlGaN/GaN HEMTs - Alim, Mohammad Abdul; Rezazadeh, Ali A.; Gaquiere, Christophe (2022 International Conference on Innovations in Science, Engineering and Technology (ICISET), 2022)
The microwave noise Figure modelling for AlGaN/GaN HEMTs is shown in this study over a large range of temperatures e.g., -40 to 150°C. Standard noise parameters for example minimum noise Figure NF min ), normalized noise equivalent resistance R s , and association gain G a were modelled at various frequencies and temperatures. The temperature coefficients of noise-related equivalent circuit parameters (ECPs) were also determined. The noise parameters of GaN on SiC based HEMTs are considered to be analogous to GaN HEMTs on Si, sapphire, and diamond substrates, as well as InP- and GaAs HEMTs. According to the findings, GaN/SiC HEMTs offer a lot of potential for applications requiring LNAs at high temperatures.